Indonesia REVIU KURIKULUM SEBAGAI UPAYA PENINGKATAN MUTU PENDIDIKAN DI SMK PGRI 6 DENPASAR: Reviu Kurikulum - Kadek Dedy Herawan (Jurnal Penjaminan Mutu, 2025)
To enhance educational quality and strengthen public trust in SMK PGRI 6 Denpasar, curriculum reviews are conducted as a key strategy. These reviews aim to identify curricular weaknesses and design appropriate improvements, thereby ensuring a responsive and contextual curriculum that supports better student learning outcomes. The process is carried out in a participatory and data-driven manner to guarantee its relevance and effectiveness. The research method employed in this study is descriptive qualitative research. The primary data were obtained from informants selected through purposive sampling. The collected data were then analyzed to generate meaningful findings that address the research problems. The findings of this study indicate that the curriculum of SMK PGRI 6 Denpasar was reviewed based on reflective achievements and the quality report in 2024. The review was carried out by examining its main components, namely intra-curricular, co-curricular, and extracurricular activities. Once the planning stage was completed and the curriculum review had been fully implemented, SMK PGRI 6 Denpasar undertook an important subsequent step, namely conducting evaluation and follow-up actions. This stage was intended to ensure that the review process yielded valid and useful results, which could then be used as the basis for producing official documents aligned with the decisions and policies to be applied in achieving the school’s vision, mission, and objectives for the 2025/2026 academic year.